Azadirachta indica as a Alternative Treatment Source for Methicillin-Resistant Staphylococcus Aureus Infections - Adamu, Aliyu; Idris, Hamza; Aliyu, Firdausi; Sule, Hafsat Ummi; Umar, Fatima Jummai; Aminu, Aminu Hamza (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
The emergence and spread of antibacterial strains of pathogenic bacteria pose a significant global health threat. This study assessed the occurrence of methicillin-resistant Staphylococcus aureus (MRSA) and its susceptibility to Azadirachta indica (neem) leaf extract. A total of 300 S. aureus isolated from wounds and burns were collected from two hospitals (Yusuf Dan Tsoho general hospital and Barau Dikko teaching hospital) within Kaduna metropolis and were screened for methicillin resistance. Occurrence rates of MRSA were found to be 28% and 18 % for wound and burn isolates, respectively. Evaluation of antibacterial activity of ethanolic and aqueous extracts of Azadirachta indica leaf against MRSA isolates using the agar well diffusion method shows positive antibacterial activity, with mean zones of inhibition ranging from 21.94 ± 2.63 mm to 9.97 ± 1.54 mm for wound isolates and 19.31 ± 3.85 mm to 8.53 ± 3.34 mm for burn isolates with The MIC and MBC of the ethanolic extract ranging from 250 mg/ml to 500 mg/ml, indicating bactericidal activity. However, no significant antibacterial activity was recorded against the aqueous extract. The results obtained from this study suggest leaf extracts of Azadirachta indica could serve as a potential source of antibacterial agents for treating methicillin-resistant Staphylococcus aureus (MRSA) infections.